Ethnoveterinary use of plants and its implication for sustainable livestock management in Nepal - Uprety, Yadav; Karki, Sangram; Poudel, Ram C.; Kunwar, Ripu M. (Frontiers in Veterinary Science, 2022)
Traditional herbal remedies are used worldwide for treating both human and livestock health issues. Though such uses are relatively well explored for humans, the ethnoveterinary uses of plant-based remedies in the healthcare choices of livestock in Nepal and associated knowledge are largely ignored. This is important as sustainable livestock production is an emerging issue. This study reviews the existing ethnobotanical studies conducted in Nepal and reports the use of 393 species of plants from 114 botanical families in ethnoveterinary practices. Thirty-four different ailments were treated using these plants. The present review revealed that Nepal has a rich diversity of ethnoveterinary plants. This study shows that traditional herbal medicine plays a significant role in meeting the livestock healthcare needs of Nepali farmers and hence is a viable practice. The study also contributes a wealth of knowledge of ethnoveterinary practices for further planning and use. This will provide an option for livestock farmers who cannot afford allopathic medicine or who are not allowed to use such medicine under organic farming schemes that are likely to be a part of sustainable livestock farming programs in Nepal soon.